Prognostic Significance of Neutrophil-to-Lymphocyte Ratio and C-Reactive Protein/Albumin Ratio in Luminal Breast Cancers With HER2-Negativity - Chen, Fei; Chen, Danzhi; Jin, Lidan; Xu, Chenpu; Zhao, Wenhe; Hu, Wenxian (Frontiers in Oncology, 2022)
Purpose: This study was determined to evaluate the prognostic value of neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein/albumin ratio (CAR) prior to surgery in luminal breast cancers (BC) with HER2-negativity. Methods: The clinical data of 708 HER2-negative luminal BC patients from January 2013 to December 2016 were retrospectively collected and analyzed. The optimal cut-off value of NLR and CAR were determined via receiver operating characteristic (ROC) curve. The disease-free survival (DFS) and cancer specific survival (CSS) rates were estimated using the Kaplan−Meier method. Cox univariate and multivariate proportional hazards regression models were performed to identify significant predictors of DFS and CSS simultaneously. Results: The mean age of the patients diagnosed was 52.43 years (range, 15–95 years), and the median follow-up was 62.71 months (range, 12-92 months). Univariate and multivariate analysis confirmed that NLR ≥2.2 was significantly associated with worse DFS (HR=2.886, 95%CI=1.756-4.745, p<0.001), and same results were obtained in terms of CSS (HR=3.999, 95%CI=2.002-7.987, p<0.001). Similarly, CAR ≥0.07 was independently and significantly associated with poor DFS (HR=3.858, 95%CI=2.346-6.345, p<0.001) and CSS (HR=6.563, 95%CI=3.558-12.106, p<0.001). Conclusion: Preoperative evaluation of NLR and CAR were significant and independent prognostic indicators for luminal breast cancers with HER2-negativity.